2009
DOI: 10.1097/jto.0b013e3181ae27f5
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Quality of Life Is an Independent Prognostic Factor for Overall Survival in Patients with Advanced Stage Non-small Cell Lung Cancer

Abstract: Hypothesis We conducted this pooled analysis to assess the prognostic value of pretreatment Quality of Life (QOL) assessments on overall survival (OS) in advanced non-small cell lung cancer (NSCLC). Methods Four hundred twenty patients with advanced NSCLC (stages IIIB with pleural effusion and IV) from six North Central Cancer Treatment Group trials were included in this study. QOL assessments included the single-item Uniscale (355 patients), Lung Cancer Symptom Scale (217 patients), and Functional Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 44 publications
(57 reference statements)
6
41
1
2
Order By: Relevance
“…Survival duration was significantly shorter for patients with the poorest well-being before treatment than for those with the best well-being (poorest: 22 weeks; 95% ci: 18 weeks to 27 weeks; best: 37 weeks; 95% ci: 31 weeks to 44 weeks). That observation is consistent with the results of previous studies that have shown the prognostic value of pretreatment qol 31 .…”
Section: Discussionsupporting
confidence: 83%
“…Survival duration was significantly shorter for patients with the poorest well-being before treatment than for those with the best well-being (poorest: 22 weeks; 95% ci: 18 weeks to 27 weeks; best: 37 weeks; 95% ci: 31 weeks to 44 weeks). That observation is consistent with the results of previous studies that have shown the prognostic value of pretreatment qol 31 .…”
Section: Discussionsupporting
confidence: 83%
“…Patients were categorized according to LASA overall QOL scores (≤50 vs >50). Previous research has indicated that this cutoff, as measured by the visual analog Spritzer Uniscale, is a prognostic factor (27). As the linear analog scale has been shown to be comparable to the visual analog scale, this categorization is valid in this study (28).…”
Section: Methodsmentioning
confidence: 99%
“…Baseline global QOL was a strong independent predictor of survival in patients with advanced CRC in one study [Maisey et al 2002], while in another study, the patient's score on the social functioning scale translated into a 9% decrease in the patient's hazard of death for any 10-point increase in the score (0 to 100 scale) [Efficace et al 2008[Efficace et al , 2006a. A correlation between various pretreatment PRO domain scores, including overall quality of life [Qi et al 2009], global quality of life [Movsas et al 2009 [Roychowdhury et al 2003] and total quality of life score in metastatic HRPC [Sullivan et al 2006] and in localized prostate cancer [Sadetsky et al 2009] have been associated with survival.…”
Section: Prediction and Prognosismentioning
confidence: 99%